A Highly Stable Biocatalyst Obtained from Covalent Immobilization of a Non-Commercial Cysteine Phytoprotease - Obregón, Walter David (2015)
In this work, araujiain (enzymatic preparation obtained from the latex of Araujia hortorum fruits) was successfully immobilized on glyoxyl-agarose via multipoint covalent attachment. Thus, good efficiency of immobilization and high operational stability of immobilized enzyme were obtained. The activity of araujiain at alkaline pH was significantly improved after immobilization. In addition, immobilized araujiain also showed high activity and good stability, without significant loss in its activity, at temperatures between 37 and 60°C and in the presence of immiscible organic solvents. Immobilized araujiain also showed good performance in a mixture of 50% ethyl acetate in buffer, used for peptide synthesis, with better results than when the free enzyme was used as catalyst. These results indicate that immobilized araujiain via multipoint covalent attachment can be highly stabilized and this method might be used for practical applications of araujiain in hydrolytic and synthetic processes.